Sustainability Analysis of Hybrid Maize Farming in Grogol District, Kediri Regency - Tazkiyah Salsabila; Rita Parmawati; Fadli Mulyadi; Dwi Retno Adriani; Budi Setiawan (The University of Lampung, 2026)
This study aims to evaluate the sustainability of hybrid maize farming in Grogol District, Kediri Regency, by considering economic, ecological, and social aspects that influence farmers’ welfare and the resilience of the agricultural system. The research employed observation, structured interviews, and questionnaire distribution, with data analyzed using the Multidimensional Scaling (MDS) method. Instrument reliability was tested through validity and reliability assessments. The findings show that the sustainability status of hybrid maize farming in the study area falls into the less sustainable category, with index scores of 44.11 for the ecological dimension, 49.15 for the economic dimension, and 46.19 for the social dimension. Leverage analysis identified that pest and disease control, market access expansion, and transportation infrastructure were the most sensitive attributes influencing each respective dimension. Moreover, Monte Carlo analysis revealed stress values below 0.5, indicating the accuracy and stability of the MDS results. These findings highlight that improvements in those key attributes are crucial for enhancing sustainability. Therefore, integrated strategies involving extension services, market development, and infrastructure improvement are essential to significantly improve the overall sustainability of hybrid maize farming in the region.